Agarolytic Bacillus sp. FRAgK1 Screened from Gracilaria (Rhodophyta) Thallus as Probiotic Candidate for Abalone - Abdullah, Faisal Zain; Istiqomah, Indah; Isnansetyo, Alim; Yasa, Ngurah Sedana; Ismail, Norshida (Universitas Gadjah Mada, 2024)
Agarolytic bacteria produce agarase, which may aid in the growth of cultured tropical abalone fed natural seaweed. Agarolytic bacteria can come from a variety of sources, such as seawater, abalone intestines, and dead seaweed. This study aimed to isolate, screen, describe, and identify agarolytic bacteria found in red macroalgae. Agarolytic bacteria isolated from Gracilaria segregated from the substrate at Drini Beach, Gunungkidul Regency, were qualitatively described using the agarolytic index, antibiotic susceptibility, acid resistance (pH 4), and safety test. We collected seven agarolytic isolates. FRAgK1 isolate had the highest agarolytic index, was sensitive to antibiotics, resistant to low pH conditions, and non-pathogenic to finfish, making it suitable for use as gut probiotics in abalone. The bacterium was short rod-shaped, Gram-positive, non-motile, lacked catalase and indol, and was unable to ferment lactose or sucrose. The 16S rRNA gene sequence of FRAgK1 was most like Bacillus subtilis, however only by 99.43%.